2016
DOI: 10.1037/hea0000375
|View full text |Cite
|
Sign up to set email alerts
|

Automatic effects of illness schema activation on behavioral manifestations of illness.

Abstract: Objective: Relatively little research has directly evaluated the schematic nature of illness representations proposed by the common sense model of illness. Four studies tested the hypothesis that illness schema activation leads directly and automatically to behavioral manifestations of illness. Methods: Study 1 was a survey (N = 970) that evaluated the proposition that the mental representation of common cold symptom experience includes functional deviation from the usual prototypical self. Studies 2 and 3 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Therefore, one can assume that even fatigue/decreased vitality exists as a schema. In several experiments, after a subliminal priming with a fatigue-involving concept (the flu), healthy people showed elevated signs of physical and mental fatigue (e.g., decreased walking speed, impaired learning and recalling; Orbell and Henderson, 2016). Shalev (2014) found in a series of experiments that people primed with thirst (a fatigued-related bodily state) had reduced perceived momentary vitality and had lower persistence in a frustrating task (a measure that has frequently been used to assess ego depletion; e.g., Baumeister et al, 1998).…”
Section: The Schema Model Of Self-controlmentioning
confidence: 99%
“…Therefore, one can assume that even fatigue/decreased vitality exists as a schema. In several experiments, after a subliminal priming with a fatigue-involving concept (the flu), healthy people showed elevated signs of physical and mental fatigue (e.g., decreased walking speed, impaired learning and recalling; Orbell and Henderson, 2016). Shalev (2014) found in a series of experiments that people primed with thirst (a fatigued-related bodily state) had reduced perceived momentary vitality and had lower persistence in a frustrating task (a measure that has frequently been used to assess ego depletion; e.g., Baumeister et al, 1998).…”
Section: The Schema Model Of Self-controlmentioning
confidence: 99%
“…On the other hand, recent experimental studies have advanced our understanding of self-regulation and provided more support to the CSM. For example, several experimental studies have demonstrated the close relationships between implicit illness schemata, illness beliefs, illness-related information and coping procedures/action plans (e.g., Ahluwalia, Hughes, McCracken, & Chilcot, 2017;Henderson, Orbell, & Hagger, 2009;Orbell & Henderson, 2016).…”
mentioning
confidence: 99%
“…In essence, the prototype of the normal self in a chronically ill patient may become enmeshed in the illness prototype so that every sensory experience is attended to and interpreted as a symptom indicative of existing illness. Orbell and Henderson (2016) suggest that illness schema activation by priming might be viewed within an active self-account (Smeesters, Wheeler & Kay, 2010;Wheeler, DeMarree & Petty, 2007). People possess a vast chronic self-concept of which only a subset can be active at any given moment, and serves to guide behaviour (Markus & Wurf, 1987).…”
Section: Automatic Processes In Individuals' Illness-threat Detectionmentioning
confidence: 99%
“…Some of these non-consciously mediated processes are behavioural correlates of biological responses to illness threat (e.g. such as resting or sleeping in association with immune function activity in response to infection, Orbell & Henderson, 2016; or immediate cessation of exertion in response to a pulled muscle during physical activity). To illustrate, consider that parents and carers recognise a state of ill health in a young child (or even a pet animal) by observation of change in a child's normal activity and temperament rather than a verbal declaration of symptoms or illness labels.…”
Section: Cognitive Accessibility Of Coping Responsesmentioning
confidence: 99%
See 1 more Smart Citation